Cyber Laws and Regulations, COVID 19, and the Battle to Combat Cybercrimes in Maharashtra India: an Empirical Inquiry - Sharma, Sushil (Indian journal of criminology, 2024)
The Covid-19 pandemic impacted all facets of social life, especially work, education, retail, and banking. To ensure business continuity, many of these sectors were forced to migrate to online platform causing a dramatic increase in global internet usage. This global trend has been equally applicable to the Indian case. Even prior to the pandemic the Indian Government had been pushing for increased digitisation through schemes such as Digital India. As such, increase in internet usage has led to many problems and challenges for police in India. This paper seeks to provide an empirical examination of cybercrimes in Maharashtra, India, during the Covid-19 pandemic and consequently study the application and efficacy of India's Information Technology (IT) Act of 2000 in terms of preventing the occurrence of these cybercrimes. The paper analyses cybercrimes under different heads: fake news/ rumours, phishing, financial frauds, etc. in various districts in Maharashtra, which is an economically prosperous Indian state with one of the highest degrees of digital penetration. Extant scholarship on the impact of the Covid-19 pandemic on cybersecurity has mostly focused on the developed world. However, this paper looks to shed light on the unique social fears and vulnerabilities exploited by cybercriminals in the Indian case, which will represent a distinct global south vantage point.